PEDAGOGIKA OLIY TA'LIM MUASSASALARIDA “KOMPYUTER GRAFIKASI” FANINI O'QITISH MUAMMO SIFATIDA - Zaripov, O.Q. (SCIENCE and SOCIETY, 2019)
The article is devoted to one of the actual issues- methods of teaching the discipline “Computer graphics” at higher educational institutions. The author of the article presents the models of teaching Computer graphics.
Keywords: computer graphics; model; education; motivation; technology; pedagogical technologies; software